ALIH KODE DAN CAMPUR KODE PADA PEMERAN UTAMA ZAINUDDIN DALAM FILM TENGGELAMNYA KAPAL VAN DER WIJCK - Fiddienika, Arief; Awaliyah, Nur Iffa; Akuba, Annisa Salsabilah (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
The purpose of this research is to describe the form and factors that cause code switching and code mixing in the movie "Tenggelamnya Kapal Van Der Wijck". This research uses a qualitative descriptive approach, the data in this study is a collection of words that make up the dialog obtained from watching the movie Tenggelamnya kapal Van Der Wicjk, using listening techniques and note-taking techniques. The results showed that Zainuddin, the main character, code-switched and code-mixed when interacting with other people. This research reveals that the use of code-switching and code-mixing reflects the flexibility and adaptability of speakers in conveying messages according to different social and cultural contexts. The movie shows how cross-cultural and linguistic interactions can occur in everyday life, enriching the understanding of sociolinguistic dynamics in a multilingual society.